A giant right atrial myxoma—The growth rate and multi‐modality imaging. Issue 6 (13th April 2021) - Hsi, David H.; Sosa, Andrew; Miller, Wayne; Oren, Tal; Koulova, Anna; Coady, Michael A.
Abstract: A young and healthy woman presented with progressive dyspnea on exertion. An echocardiogram showed a giant right atrial mass. Cardiac CT angiography provided the most accurate estimate for the tumor size, while 2‐D echo, 2‐D, and 3‐D trans‐esophageal echo underestimated the dimensions of the cardiac tumor when referenced by the surgical specimen. We also calculated the growth rate of the right atrial myxoma to be at least 1.2 mm per month based on a normal chest CT 54 months before her presentation. Surgical pathology confirmed typical features of cardiac myxoma in the right atrium.